CLIL in Education for Science: a case study in a (post-) graduate program - Concário, Marcelo [UNESP]; Martins, Ana Elisa Piedade Sodero [UNESP]; Ignácio, Ismair [UNESP] (Programa de Pós-Graduação em Educação para a Ciência, Universidade Estadual Paulista (UNESP), Faculdade de Ciências, campus de Bauru., 2022)
Content and language integrated learning (CLIL) has a long tradition in European countries, especially in primary and secondary education. In this paper we draw attention to the limited use of the term in higher education, especially at (post-)graduate level. By describing and discussing a course entirely taught in English to students in a program titled Education for Science in Brazil, the authors expect to contribute to a broader understanding of the interrelations between specialized content and advanced communicative skills in English for academic purposes. By focusing on qualitative data on the collaborative writing of a paper in English, it is expected that this kind of classroom-based case study will contribute to better informed decisions related to internationalization of (post-)graduate programs among institutions that underscore the importance of English to help promote visibility and cooperation.

A aprendizagem integrada de conteúdos e de línguas (AICL) tem grande tradição na educação básica europeia. Neste artigo chamamos atenção para o uso indevidamente limitado do termo no ensino superior, sobretudo na pós-graduação. Ao descrever criticamente ações em uma disciplina num programa de pós em Educação para a Ciência, integralmente realizadas em inglês, buscamos contribuir para uma compreensão mais ampla das inter-relações entre conteúdos especializados e competências comunicativas avançadas em inglês acadêmico. Com base em dados qualitativos sobre a escrita colaborativa deste artigo em inglês, esperamos que o estudo de caso em sala de aula possa promover decisões mais amadurecidas quanto à internacionalização de programas de pós nas instituições que enfatizam a importância da língua inglesa para a visibilidade e cooperação acadêmica.
CLIL em Educação para a Ciência: um estudo de caso em um programa de pós-graduação
Keywords: English for specific purposes; (Post-)graduate education; Academic language functions; Ensino de inglês; CLIL; AICL; Educação para a ciência; Ensino superior